Recent Developments in Direct C–H Functionalization of Quinoxalin-2(1H)-Ones via Heterogeneous Catalysis Reactions - Qiming Yang; Hu Wang; Xiang Wang; Yizhu Lei (Molecules, 2023)
In recent years, Web of Science has published nearly one hundred reports per year on quinoxalin-2(1H)-ones, which have attracted great interest due to their wide applications in pharmaceutical and materials fields, especially in recyclable heterogeneous catalytic reactions for direct C–H functionalisation. This review summarises for the first time the methods and reaction mechanisms of heterogeneous catalytic reactions of quinoxalin-2(1H)-ones, including six major types of heterogeneous catalysts involved. The heterogeneous reactions of quinoxalin-2(1H)-ones are summarised by classifying different types of catalytic materials (graphitic phase carbon nitride, MOF, COF, ion exchange resin, piezoelectric materials, and microsphere catalysis). In addition, this review discusses the future development of heterogeneous catalytic reactions of quinoxalin-2(1H)-ones, including the construction of C-B/Si/P/RF/X/Se bonds by heterogeneous catalytic reactions, the enrichment of heterogeneous catalysts such as metal oxides, graphene-based composites, doped metal nanoparticles, and molecular sieve-based porous materials, asymmetric synthesis, and other areas. The aim of this review is to contribute to the development of green and sustainable heterogeneous reaction methods for quinoxalin-2(1H)-ones with applications in materials chemistry and pharmacology.